Popular use of medicinal plants in the municipality of Tefé, Amazonas, Brazil. (Research, Society and Development, 2022)
Medicinal plants are natural products used since ancient times, and the knowledge regarding their properties and use is transferred from one generation to the next. Many people continue to consume this natural product, which has made this means of treatment relevant in the eyes of researchers. The search for this learning using the collection of information as a source is increasingly growing, thus allowing to study their properties, their therapeutic powers, and active principles. For this reason, this work aimed to collect, analyze and record information about the level of knowledge of the population about pre-established medicinal plants, their origin, the form of use and the pharmacological effects of these species cultivated in the municipality of Tefé-Amazonas, Brazil. The collection of information took place through an interview, which contained questions regarding the plants: pobre-velho (Costus spicatus), escada de jabuti (Bauhinia rutilans), mucuracaá (Petiveira alliacea), sucuuba (Himatantuhs sucuuba) and panquelé (Piper amapens). The data collected had satisfactory results where it was observed that a large part of the population knows and makes use of the plants mentioned and often the same plant is used for different pathologies. Another relevant point is that some plants are known with different names, and many people did not recognize them by the names mentioned, which made the answers of the interviews inaccurate at times, however, did not compromise the results. Therefore, the knowledge of the population has great relevance for the enrichment of knowledge about natural products, where many scholars are able to discover and develop products that are essential for curing, treating or preventing diseases that are often referred to as irremediable.